The effect of quick response manufacturing in supply chain activities: A case study of automotive company in Malaysia - Yusoof, M. Y. M.; Nik Mohamed, N. M. Z.; Azhar, Ahmad Syafiq Jazatul; Nelfiyanti, . (Springer, 2021)
The new era of industrial revolution 4.0, requires a lot of improvement especially in automotive assembly line. A poor flow on supply chain especially on logistic in the company affect the company performance. Insufficient planning may lead to less efficiency, quality and productivity loss. The objective of this study is to improve the critical supply chain in the automotive industry by studying the current data given by the company and used it to simulate on WITNESS. The output from the current simulation will determine on how to improve the supply chain by doing some changes in which lead to the optimized condition. After series of simulations, the output shows improvement especially on idle time and busy time. The idle time that possessed was under 20% while the busy time between 70% until 90% across the mechanical and trim sections.